Android-Based Diabetes Foot Care Education Application: A User Satisfaction Study on Various Demographic Profiles - Suyanto, Suyanto; Astuti, Sri Lestari Dwi; Rohimah, Yeni Tutu; Suryanti, Suryanti (Jurnal Pendidikan MIPA, 2025)
Abstract: Smartphone educational applications have been developed as an alternative when educating patients. Although many similar applications have been developed, they focus on services and information about diabetes management. For this reason, this research aims to create an educational application in an Android-based smartphone called Rawat focused on diabetic foot wound prevention care. This is based on the fact that the incidence of foot wounds can be prevented by conducting education. Seeing that application users have diverse demographic profiles. It must be a concern that all users benefit so that educational goals can be achieved. Therefore, it is necessary to examine users' satisfaction with foot wound application seen from various demographic profiles. The research design used a Descriptive Comparative, purposive sampling technique with a total sample of 140 respondents as members of Persadia (Indonesian Diabetes Association) at RSUD: Salatiga City, Surakarta City, Surakarta Regency, Prambanan Yogyakarta and Klaten Islamic Hospital. Data were collected using the EUCS questionnaire and analyzed using the Chi Square test and Logistic Regression. The results showed that there was no difference in satisfaction with the Rawat Kaki application in the job profile. For the education, job and age profiles, there were differences in satisfaction. The profiles that were closely related to influencing respondent satisfaction were gender, education and age, while work had no effect.       Keywords: diabetics, demographics, android app, satisfaction.